2014
DOI: 10.1159/000363500
|View full text |Cite
|
Sign up to set email alerts
|

Agitation in Dementia: Relation to Core Cerebrospinal Fluid Biomarker Levels

Abstract: Background: The objective of this study was to examine the associations of agitation with the cerebrospinal fluid dementia biomarkers total-tau (T-tau), phosphorylated-tau (P-tau) and Aβ1-42. Methods: One hundred patients (mean age ± SD, 78.6 ± 7.5 years) with dementia and neuropsychiatric symptoms, of whom 67% were female, were included. Agitation was measured using the Cohen-Mansfield Agitation Inventory (CMAI; 46.5 ± 11.8 points). Results: Total CMAI correlated with T-tau [rs (31) = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 33 publications
(46 reference statements)
2
20
0
Order By: Relevance
“…For our secondary objective, we tested whether CSF markers may predict the course of NPS and found some indications that the course of some specific neuropsychiatric symptoms was associated with baseline CSF markers. We recently reported that Tau-mediated pathology was associated with increased agitation in AD [11]. In this study, low Aβ 1–42 at baseline was associated with improvement of irritability during treatment.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…For our secondary objective, we tested whether CSF markers may predict the course of NPS and found some indications that the course of some specific neuropsychiatric symptoms was associated with baseline CSF markers. We recently reported that Tau-mediated pathology was associated with increased agitation in AD [11]. In this study, low Aβ 1–42 at baseline was associated with improvement of irritability during treatment.…”
Section: Discussionsupporting
confidence: 48%
“…Pre-analytic and analytic procedures have been described in detail elsewhere [11]. In brief, T-tau concentration in CSF was determined using a sandwich ELISA (Innotest hTAU-Ag, Innogenetics, Gent, Belgium) [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the measurement usually reflects only the state at the time point (snapshot) the sample was obtained and different pathological situations show a distinct secretion pattern. Most importantly, in the majority of clinical evaluations, more than one biomarker needs to be available to support the interpretation of the activation state and clinical course [3] . Profiling these soluble factors is an important part in routine diagnostics for intensive care units and as a safety and exploratory parameter in clinical studies to obtain the current stage of the immune response after infections, vaccination or therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence on the neurobiological substrates of agitation in AD has led to investigation of repositioned and novel therapeutics for these NPS in dementia as an alternative to antipsychotics [1,5]. Central synaptic or circuit disconnections in frontal-subcortical and corticocortical networks, dysfunction in ascending monoaminergic systems involving serotonin, norepinephrine, or dopamine neurons, glutamate-mediated excitatory neurotoxicity, tau-mediated pathology, and inflammatory mediators may have a role for the development of NPS in AD [1,5,9,[35][36][37][38]. These CNS dysfunctions may occur concurrently and mediate synergistically NPS onset.…”
Section: Current and Alternative Pharmacological Approaches To The Trmentioning
confidence: 99%